Chemical characterization of the water-soluble organic nitrogen in the maritime aerosol. (January 2023) - Matsumoto, Kiyoshi; Yamamoto, Yuya; Kim, Sungben; Irino, Tomohisa; Yoshikawa-Inoue, Hisayuki
Abstract: In order to clarify the compound composition of the water-soluble organic nitrogen (WSON) in aerosols, simultaneous measurements of the WSON, free amino acids (FAA), combined amino acids (CAA), amines, and urea in the total suspended particles (TSP) were conducted at a remote coastal site located in the northern tip of Japan. About 15% of the water-soluble total nitrogen (WSTN) in the TSP was explained by the WSON, which suggests a significant contribution of the WSON to the bioavailable nitrogen in the TSP. About 22% of the WSON in the TSP can be explained by the FAA and CAA. Especially, the CAA showed about a 3.4-times higher concentration than the FAA and contributed about 17% of the WSON. The CAA would be a major compound group for the WSON in the TSP. The contribution of urea to the WSON was significant as a single compound; about 5% of the WSON in the TSP was explained by urea. In contrast, the contribution of amines to the WSON in the TSP was low. These four compound groups contributed about 29% of the WSON in the TSP. The contribution of the organic nitrogen compounds other than these four species to the WSON increased as the concentration of the WSON increased, which suggests that the high concentrations of the WSON in the TSP were significantly affected by the organic nitrogen compounds other than amino acids, amines, and urea. Highlights: The WSON contributed 15% of the WSTN in the TSP. About 22% of the WSON was explained by amino acids (the FAA and CAA). The concentration of the CAA was about 3.4-times higher than that of the FAA. About 30% of the WSON can be explained by amino acids, amines, and urea. Compounds other than amino acids, amines, and urea caused high WSON concentrations.